The Child's Voice in Adult-Led Healthcare Research: One Child Doesn't Fit All! - Bryan, Gemma; Gibson, Faith; Aldiss, Susie (Comprehensive Child & Adolescent Nursing, 2025)
The involvement of children and young people themselves, rather than that of their caregivers, in healthcare research that affects them, has increasingly been recognized as essential. However, the significance of children and young people being experts by experience, when participating in and shaping research has received less attention. This article discusses findings from the British-English Linguistic Validation Study of Sisom. Sisom is an interactive computerized symptom assessment and communication intervention that helps ill children convey their physical, functional and psychosocial symptoms and problems and assists their caregivers to better understand these issues and respond with appropriate care. When using Sisom, children first create an avatar and then sail around an archipelago of five islands ("at the hospital," "about managing things," "my body," "thoughts and feelings," "things one might be afraid of"). Each island represents a potential problem for the child. In this study, we linguistically validated the British-English version of Sisom, by first recruiting a convenience sample of "healthy" children and later a sample of children with cancer. Children were asked to review the symptom pictures and symptom terms used within Sisom to check they were easy to understand. Even after the removal of cancer-specific terms, there were still terms that "healthy" children did not know, as they lacked a frame of reference. Some symptom terms about bodily functions caused visible embarrassment for "healthy" children; this was not observed in children with cancer. The involvement of "healthy" children as proxies for children with cancer proved to be insufficient in our study. Our findings illustrate the importance of consulting with children and young people with lived experience, how children and young people can only be an expert by experience on their individual circumstances, and why recruiting or consulting "healthy" proxies for children and young people with health conditions is not enough. We should not expect children to speak as a collective. They are not a homogeneous group. Researchers should be aware of the potential implications for their study of not involving such experts with experience in each stage of their research.